2012
DOI: 10.1007/s10661-012-2679-9
|View full text |Cite
|
Sign up to set email alerts
|

Larval abundance and its relation to macrofouling settlement pattern in the coastal waters of Kalpakkam, southeastern part of India

Abstract: The present work revealed that salinity, water temperature, and food availability were the most crucial factors affecting the abundance of larvae and their settlement as macrofouling community in the coastal waters of Kalpakkam. Quantitative as well as qualitative results showed that late post-monsoon (April-May) and pre-monsoon (June-September) periods were found to be suitable periods for larval growth, development, and survival to adult stages for most of the organisms. Clustering of physico-chemical and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
1
0
1
Order By: Relevance
“…In fact, it has been shown that salinity influences all physical-chemical variables of seawater and controls the larval dispersal and recruitment patterns of epi-and endobiotic species (Nair 1965), while seawater temperature influences chemical and biological interaction and regulates the growth of benthic organisms (Sahu et al 2013). Consequently, the shells of smaller gastropods are usually less colonized by epifauna than those of larger gastropods, which also agrees with our observations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In fact, it has been shown that salinity influences all physical-chemical variables of seawater and controls the larval dispersal and recruitment patterns of epi-and endobiotic species (Nair 1965), while seawater temperature influences chemical and biological interaction and regulates the growth of benthic organisms (Sahu et al 2013). Consequently, the shells of smaller gastropods are usually less colonized by epifauna than those of larger gastropods, which also agrees with our observations.…”
Section: Discussionsupporting
confidence: 91%
“…Fouling is likely to be a function of time, food availability, seawater salinity and temperature (Wahl 1989, Sahu et al 2013. In fact, it has been shown that salinity influences all physical-chemical variables of seawater and controls the larval dispersal and recruitment patterns of epi-and endobiotic species (Nair 1965), while seawater temperature influences chemical and biological interaction and regulates the growth of benthic organisms (Sahu et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Macro fouler's distribution and diversity in Port Blair, Andaman and Nicobar Islands were carried by Deepa et al, 2015. They also similarly reported the Balanus spp were dominant in all stations and arthropods and mollusks are predominant in fouling community. Our study in concurrent with the results of Sahu et al, 2015 who studied the biofouling diversity at Kalpakkam coastal waters and found that the barnacle sp. is pioneer as macro foulers and Perna viridis was climax in this community.…”
Section: Discussionsupporting
confidence: 89%
“…Biofouling causes great operational hazards in different marine artificial structures across the globe. Biofouling reported that Shut down of 235 MW power station (Sahu et al, 2015). Although a plethora of research has been carried out on biofouling organisms in and around world, most of the studies were focused on antifouling strategies (Dehmordi et al, 2011;Deepa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Por lo tanto, llevar a cabo una metodología para controlar estos organismos en diferentes etapas de la vida es de suma importancia. En seis estudios analizados se abordaron las diferentes etapas de vida de los mejillones (Folino-Rorem, et al, 2006;Matsuo, et al, 2009;Schaefer, et al, 2010;Sahu, et al, 2013;Yuan, et al, 2016).…”
Section: ¿El Propósito De Los Trabajos Fue Controlar Larvas O Mejillo...unclassified